2019
DOI: 10.1097/md.0000000000015111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation with intravascular laser on the hemodynamic variables of hypertensive patients

Abstract: Background: High blood pressure (HBP) is a multifactorial clinical condition, with a high morbidity and mortality rate and low rates of control. Due to its high prevalence, it is necessary to search for methods which aim to improve the quality of life of hypertensive patients. Studies have shown that low level laser therapy (LLLT) is capable of inducing a photobiological response within the cells which modifies the micro and macrovascular response; this accompanies evidence showing the systemic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Khalighi et al [7] reported that low-level laser therapy alters impulses in the dorsal horn and inhibits pain in the cerebral cortex, balances levels of the neurotransmitters epinephrine and norepinephrine, increases serotonin and glucocorticoid excretion, and increases levels of β-endorphin, all hormones directly associated with anxiety. Isabella et al [8], Mikhaylov [9], and Huang et al [10] noted that photoreception of low-level ILIB energy, when applied systemically, is carried by hemoglobin and activates substances such as superoxide dismutase, nitric oxide synthase, catalase, and cytochrome c. These substances interfere with ATP production and alter the plasma membrane by sending information to the neurohumoral regulation system. This response cascade affects the autonomic nervous system, inhibits synthesis of prostaglandins that cause inflammation, and modulates hormones that interfere with anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Khalighi et al [7] reported that low-level laser therapy alters impulses in the dorsal horn and inhibits pain in the cerebral cortex, balances levels of the neurotransmitters epinephrine and norepinephrine, increases serotonin and glucocorticoid excretion, and increases levels of β-endorphin, all hormones directly associated with anxiety. Isabella et al [8], Mikhaylov [9], and Huang et al [10] noted that photoreception of low-level ILIB energy, when applied systemically, is carried by hemoglobin and activates substances such as superoxide dismutase, nitric oxide synthase, catalase, and cytochrome c. These substances interfere with ATP production and alter the plasma membrane by sending information to the neurohumoral regulation system. This response cascade affects the autonomic nervous system, inhibits synthesis of prostaglandins that cause inflammation, and modulates hormones that interfere with anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The application of LED to the masticatory muscles affects the local tissues around the light application site and previous studies have shown the effectiveness of LED treatment in muscle tissues [ 26 , 27 , 28 ]. The literature also reports that it is possible to observe systemic responses through light therapy, with the action of deep light stimulation directly on the brain [ 29 ]. Another application of the method involves the intravascular laser irradiation for blood therapy, which has already shown good results [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the second hypothesis, ILIB affects the rheological behavior of blood, diminishes platelet aggregation, and improves the deformability of red blood cells, all of which lead to better oxygen delivery to the hypoxic or infarcted areas caused by CO intoxication. Vasodilatation also ensues as a result of increased nitric oxide released from monocytes[ 24 ]. Third, according to Huang et al [ 8 ], ILIB alleviates both mitochondrial dysfunction and oxidative stress through the regulation of mitochondria numbers and metabolic enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%